2014
DOI: 10.1186/gb-2014-15-6-r79
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analysis of Apobec-1-mediated C-to-U RNA editing in mouse small intestine and liver

Abstract: BackgroundRNA editing encompasses a post-transcriptional process in which the genomically templated sequence is enzymatically altered and introduces a modified base into the edited transcript. Mammalian C-to-U RNA editing represents a distinct subtype of base modification, whose prototype is intestinal apolipoprotein B mRNA, mediated by the catalytic deaminase Apobec-1. However, the genome-wide identification, tissue-specificity and functional implications of Apobec-1-mediated C-to-U RNA editing remain incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 52 publications
11
108
1
Order By: Relevance
“…2B; Supplemental Table S5). Consistent with previous observations (Blanc and Davidson 2011;Danecek et al 2012;Gu et al 2012;Blanc et al 2014), we observed that the majority (all = 77.3% and clustered = 80%) of the DRE sites resided in the 3 UTR of the gene , while 21.9% of all DRE sites and 11.1% of the clustered DRE sites resided in the protein coding regions of the gene (Fig. 2B).…”
Section: Consequence Analysis Of Dre Sitessupporting
confidence: 80%
“…2B; Supplemental Table S5). Consistent with previous observations (Blanc and Davidson 2011;Danecek et al 2012;Gu et al 2012;Blanc et al 2014), we observed that the majority (all = 77.3% and clustered = 80%) of the DRE sites resided in the 3 UTR of the gene , while 21.9% of all DRE sites and 11.1% of the clustered DRE sites resided in the protein coding regions of the gene (Fig. 2B).…”
Section: Consequence Analysis Of Dre Sitessupporting
confidence: 80%
“…The few identified physiological C-to-U RNA editing targets include apolipoprotein B (apoB) pre-mRNA in intestinal cells and several recently validated, but uncharacterized mRNA targets; in an early study, 32 previously unknown APOBEC1 (apoB editing catalytic subunit 1) editing sites in the 3' untranslated regions (3' UTRs) of diverse mRNA transcripts were identified and validated (11). In addition, 56 novel editing sites in 54 intestinal mRNAs and 22 novel sites in 17 liver mRNAs in AU-rich segments of the 3' UTRs were also identified (12). Recently, 410 C-to-U RNA editing events across 275 transcripts were also found in bone marrow-derived macrophages, and nearly all (97%) of these C-to-U events were detected in the 3' UTRs (13).…”
Section: C-to-u Rna Editing In Mammalsmentioning
confidence: 99%
“…The functional relevance of all of the A1-associated RBPs is not yet fully understood, but they may participate in a variety of RNA-processing events by A1. In fact, large-scale sequence analyses by two independent groups recently revealed novel A1-specific C-to-U editing signatures in the UTR of a dozen mRNAs (55,56). Therefore, the dimeric form of AID, like that of A1, may form an as-yet unidentified RNAediting complex(es) in association with its CSR-specific RBP Before the co-IP analysis, the cell lysates were either untreated or treated with RNase A or 500 mM NaCl.…”
Section: Discussionmentioning
confidence: 99%